2019
DOI: 10.1080/20008198.2019.1603557
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and risk for suicide attempts in major depression: a sex-specific approach

Abstract: Background : Childhood maltreatment increases the risk of suicide attempts in the general population, possibly having similar effects among patients with major depressive disorder (MDD). The few studies that have addressed this association have been restricted to specific populations (e.g. treatment-resistant depression, personality disorders) and have rarely taken sex into account. Objective : To examine the impact of childhood maltreatment on suicide attempts among MDD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 73 publications
1
14
0
1
Order By: Relevance
“…, 2010 ) and is associated with worse psychiatric outcomes ( Melhem et al. , 2019 ), particularly in women ( Goldberg et al. , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2010 ) and is associated with worse psychiatric outcomes ( Melhem et al. , 2019 ), particularly in women ( Goldberg et al. , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies focused on specific clinical and personality factors that might enhance the likelihood of suicidal behavior. For instance, these studies found an association between suicide attempts and the presence of psychiatric disorders (4)(5)(6), greater hopelessness (6, 7), higher level of impulsivity and aggression (8,9) and the presence of childhood trauma (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies with MDD patients did not find any specific type of trauma associated with SA. 40 More research is needed to better understand the role of each type of trauma in the suicide model. 2 Suicidal ideation beginning at an early age and the existence of previous and/or present suicidal plans are the main risk factors for the first SA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with MDD patients did not find any specific type of trauma associated with SA. 40 More research is needed to better understand the role of each type of trauma in the suicide model. 2 …”
Section: Discussionmentioning
confidence: 99%